The HERO project: language training for migrants’ professional career as caregivers through blended learning - Soule, Maria Victoria; Stylianou, Kostas; Yerou, Christina; Xerou, Eftychia; Tsitsi, Theologia; Charalambous, Andreas (My University, 2021)
The HERO project aims to develop a training program for caregivers to be working in the elderly care sector. The program is particularly addressed to caregivers from Middle Eastern and African countries as refugees and intends to help them integrate into European society. This paper seeks to offer an overview of the project, including its objectives, underlying principles, and deliverables. The paper particularly portrays the second intellectual output (O2) of the project, namely the ‘On the job’ training in language and terminology curriculum, which has been developed as the end product of O2. Initially, the methodology adopted to create learning material for language learning in a specific-purpose context is analyzed. Based on this, the paper provides a description of the content development by justifying and showcasing the learning material and laying out the logic behind this, through the trainers’ guide. E-learning tools have been integrated in the course material, which also justifies the methodology applied for the purpose of this project.
Keywords: professionalization; migration; languages for specific purposes; blended learning